Molecular analysis of a novel family of complex glycoinositolphosphoryl ceramides from Cryptococcus neoformans: structural differences between encapsulated and acapsular yeast forms. - Heise, N; Gutierrez, A; Mattos, K; Jones, C; Wait, R; Previato, J; Mendonça-Previato, L (2002)
Complex glycoinositolphosphoryl ceramides (GIPCs) have been purified from a pathogenic encapsulated wild-type (WT) strain of Cryptococcus neoformans var. neoformans and from an acapsular mutant (Cap67). The structures of the GIPCs were determined by a combination of tandem mass spectrometry, nuclear magnetic resonance spectroscopy, methylation analysis, gas chromatography-mass spectrometry, and chemical degradation. The main GIPC from the WT strain had the structure Manp(alpha1-3)[Xylp(beta1-2)] Manp(alpha1-4)Galp(beta1-6)Manp(alpha1-2)Ins-1-phosphoryl ceramide (GIPC A), whereas the compounds from the acapsular mutant were more heterogeneous in their glycan chains, and variants with Manp(alpha1-6) (GIPC B), Manp(alpha1-6) Manp(alpha1-6) (GIPC C), and Manp(alpha1-2)Manp(alpha1-6)Manp(alpha1-6) (GIPC D) substituents linked to the nonreducing terminal mannose residue found in the WT GIPC A were abundant. The ceramide moieties of C. neoformans GIPCs were composed of a C(18) phytosphingosine long-chain base mainly N-acylated with 2-hydroxy-tetracosanoic acid in the WT GIPC while in the acapsular Cap67 mutant GIPCs, as well as 2-hydroxy-tetracosanoic acid, the unusual 2,3-dihydroxy-tetracosanoic acid was characterized. In addition, structural analysis revealed that the amount of GIPC in the WT cells was fourfold less of that in the acapsular mutant.